Hybrid Nature of Metastable Nonradiative Recombination Centers in Perovskites : Merging Shallow and Deep Defect States - Tarasevich, Aleksandr O.; Li, Jun ; 0000-0002-0274-3989; Kniazeva, Maria A.; Eremchev, Ivan Yu; Scheblykin, Ivan G. ; 0000-0001-6059-4777 (PRX Energy, 2025)
Metastable nonradiative centers (supertraps) are significant energy loss channels in perovskite optoelectronic devices. In their active state, supertraps induce substantial energy loss through nonradiative recombination of free charge carriers. Transitions between active (energy loss) and passive (no energy loss) states result in photoluminescence (PL) blinking on timescales from milliseconds to seconds. The presence of blinking allowed us to investigate the active states of supertraps by extracting their time-dependent quenching efficiency functions on microsecond timescales from PL decay kinetics. These functions, unique to each supertrap, reveal how transitions from passive to active states modify the PL decay curve. Surprisingly, microcrystals often contain supertraps with different properties that effectively quench PL on different timescales relative to the excitation pulse: some start to quench the prompt PL immediately after excitation, while others effectively quench only the delayed PL after several microseconds. This leads to significant differences in PL blinking behavior when comparing prompt and delayed PL components. All these are inconsistent with the common view on the active state of a supertrap as a single deep energy level in the band gap. Instead, we suggest that the active state is a complex nonradiative center comprising a shallow and a deep energy level. These two-level centers likely form through the temporary association of individual defects, with variations in their quenching dynamics attributed to differences in energy levels, geometry, and local environment. By identifying supertraps with distinct time-dependent quenching dynamics, this work provides insights into defect engineering strategies that could reduce nonradiative losses in optoelectronic perovskite devices.
Publisher Copyright: © 2025 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the "https://creativecommons.org/licenses/by/4.0/"Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI. Funded by "https://www.kb.se/samverkan-och-utveckling/oppen-tillgang-och-bibsamkonsortiet/bibsamkonsortiet.html"Bibsam.